Systematic Review on the Involvement of the Kynurenine Pathway in Stroke: Pre-clinical and Clinical Evidence - Colpo, Gabriela D.; Venna, Venugopal R.; McCullough, Louise D.; Teixeira, Antonio L. (Frontiers in Neurology, 2019)
Background: Stroke is the second leading cause of death after ischemic heart disease and the third leading cause of disability-adjusted life-years lost worldwide. There is a great need for developing more effective strategies to treat stroke and its resulting impairments. Among several neuroprotective strategies tested so far, the kynurenine pathway (KP) seems to be promising, but the evidence is still sparse. Methods: Here, we performed a systematic review of preclinical and clinical studies evaluating the involvement of KP in stroke. We searched for the keywords: (“kynurenine” or “kynurenic acid” or “quinolinic acid”) AND (“ischemia” or “stroke” or “occlusion) in the electronic databases PubMed, Scopus, and Embase. A total of 1,130 papers was initially retrieved. Results: After careful screening, forty-five studies were included in this systematic review, being 39 pre-clinical and six clinical studies. Despite different experimental models of cerebral ischemia, the results are concordant in implicating the KP in the pathophysiology of stroke. Preclinical evidence also suggests that treatment with kynurenine and KMO inhibitors decrease infarct size and improve behavioral and cognitive outcomes. Few studies have investigated the KP in human stroke, and results are consistent with the experimental findings that the KP is activated after stroke. Conclusion: Well-designed preclinical studies addressing the expression of KP enzymes and metabolites in specific cell types and their potential effects at cellular levels alongside more clinical studies are warranted to confirm the translational potential of this pathway as a pharmacological target for stroke and related complications.